(untitled) (Scientific journal of the Fergana State University, 2023)
The article studies the well-known to all of us today the localization of drilling fluids used in the process of extraction of raw materials necessary for the oil and gas industry, and their physicochemical properties. The study of new sites, especially when carrying out exploration work in these areas, the abundance of salt layers, which negatively affects labor productivity. The excavation of these layers requires the use of special, i.e., salt-resistant, drilling fluids. Therefore, in our research work, we studied the heat and salt resistance of drilling fluids prepared on the basis of oil refinery waste adsorbents and local clays, and substantiated the need to use this solution on a large scale.